Association of Jump-Landing Biomechanics With Tibiofemoral Articular Cartilage Composition 12 Months After ACL Reconstruction. Issue 7 (20th July 2021) - Pfeiffer, Steven J.; Spang, Jeffrey T.; Nissman, Daniel; Lalush, David; Wallace, Kyle; Harkey, Matthew S.; Pietrosimone, Laura S.; Padua, Darin; Blackburn, Troy; Pietrosimone, Brian
Background: Excessively high joint loading during dynamic movements may negatively influence articular cartilage health and contribute to the development of posttraumatic osteoarthritis after anterior cruciate ligament reconstruction (ACLR). Little is known regarding the link between aberrant jump-landing biomechanics and articular cartilage health after ACLR. Purpose/Hypothesis: The purpose of this study was to determine the associations between jump-landing biomechanics and tibiofemoral articular cartilage composition measured using T1ρ magnetic resonance imaging (MRI) relaxation times 12 months postoperatively. We hypothesized that individuals who demonstrate alterations in jump-landing biomechanics, commonly observed after ACLR, would have longer T1ρ MRI relaxation times (longer T1ρ relaxation times associated with less proteoglycan density). Study Design: Cross-sectional study; Level of evidence, 3. Methods: A total of 27 individuals with unilateral ACLR participated in this cross-sectional study. Jump-landing biomechanics (peak vertical ground-reaction force [vGRF], peak internal knee extension moment [KEM], peak internal knee adduction moment [KAM]) and T1ρ MRI were collected 12 months postoperatively. Mean T1ρ relaxation times for the entire weightbearing medial femoral condyle, lateral femoral condyle (global LFC), medial tibial condyle, and lateral tibial condyle (global LTC) were calculated bilaterally. Global regions of interest were further subsectioned into posterior, central, and anterior regions of interest. All T1ρ relaxation times in the ACLR limb were normalized to the uninjured contralateral limb. Linear regressions were used to determine associations between T1ρ relaxation times and biomechanics after accounting for meniscal/chondral injury. Results: Lower ACLR limb KEM was associated with longer T1ρ relaxation times for the global LTC (Δ R 2 = 0.24; P = .02), posterior LTC (Δ R 2 = 0.21; P = .03), and anterior LTC (Δ R 2 = 0.18; P = .04). Greater ACLR limb peak vGRF was associated with longer T1ρ relaxation times for the global LFC (Δ R 2 = 0.20; P = .02) and central LFC (Δ R 2 = 0.15; P = .05). Peak KAM was not associated with T1ρ outcomes. Conclusion: At 12 months postoperatively, lower peak KEM and greater peak vGRF during jump landing were related to longer T1ρ relaxation times, suggesting worse articular cartilage composition.